The Effect Of Human Resources Competency On The Performance Of Micro, Small, and Medium Enterprises Assisted By The Cooperative And MSME Office Of Pangkep Regency - Vira Afrianti Sam; Andi Aslinda; Muhammad Luthfi Siraj (Public Resource Innovation Management and Excellence, 2026)
This study examines the effect of human resource competence on the performance of micro, small and medium enterprises assisted by the Cooperative and MSME Office of Pangkep Regency. The purpose of this study was to determine the competence of human resources in micro, small and medium enterprises assisted by the Cooperative and MSME Office of Pangkep Regency, to determine the performance of micro, small and medium enterprises assisted by the Cooperative and MSME Office of Pangkep Regency, and to determine the influence of HR competence on business performance. micro, small and medium enterprises assisted by the Department of Cooperatives and MSME in Pangkep Regency. This research approach is quantitative. This research was carried out on SMEs which are fostered by the Pangkep Regency Cooperative and MSME Office. The source of the data in this study was MSME actors who were assisted by the Pangkep District Cooperative and MSME Office. The sample used was 38 people. Data collection techniques in the form of observation, questionnaires, and documentation. Data analysis techniques include validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis.The results of the study show that the indicators used for each of these variables indicate where human resource competence is in the very good category. Indicators on the MSME performance variable are in the very good category. Based on the test of the determinant coefficient, the influence is very strong or very high between the two variables. So it can be concluded that the influence of HR competence on the performance of micro, small and medium enterprises assisted by the Cooperative and MSME Office in Pangkep Regency is very strong or very high.